FORMATION OF A FLEXIBLE VOLUME-SPATIAL ORGANIZATION OF RESIDENTIAL BUILDINGS TAKING INTO ACCOUNT THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Petrenko, Ulyana; Buravchenko, Serhiy (Theory and practice of design, 2023)
The purpose of the article was to analyze the new functional possibilities of residential construction under the condition of ensuring the adaptability of planning. To discover that flexibility in construction is able to realize its full potential and that means much more than endless changes. This much broader intention is realized by considering flexibility in issues of modernism, finance, participation in sustainable development and technology. Methodology. The advanced techniques in design are analyzed, which make it possible to formulate the functions of the elements of the interior space differently, such as the ceiling, windows, walls, etc.: they should be easily amenable to movement and other necessary modifications, creating a more flexible space. It was established that the rigid fastening of the walls is the main obstacle that demotivates the expansion of the living space and is one of the reasons for the short service life of the buildings. The idea of sustainable construction in this case is considered as a starting point, since it is about the ability to combine different functions and adapt to changes. The results. It is determined that the integration of sustainability and affordability into the housing unit meets the needs of the current generation and does not limit the right of future generations to meet their housing needs and demands. Sustainable development in design is considered as a way to achieve a better quality of life through efficient use of resources and social progress while maintaining stable economic growth and care for the environment. It was found that the availability of materials and technologies play an important role in promoting the concept of flexible construction around the world. Scientific novelty. A number of conditions have been formed, which are the reason why the majority of modern housing is built inflexible and unpromising. From the point of view of ecology, resources and socio-economic considerations, it has been found that the durability of buildings is necessary. It was determined that in economically difficult times, the city needs buildings that can easily adapt to changes in the market in order to continue functioning effectively. The close relationship between flexibility and multi-functionality was traced and their interdependence was revealed. This symbiosis creates many planning problems, as all functions require different qualities of space. Practical significance. The concept of sustainable development is based on the combination of three global components: economic, social and environmental. A huge role in the implementation of this concept is played by architecture as a universal product and material good. The task of residential architecture of the 21st century, in addition to providing comfortable conditions for all types of life, is to create an opportunity to quickly adapt to all possible changes and conditions of use and to be a connecting link between all components of the concept of sustainable development.